Fusobacterium Septicemia with Liver and Lung Abscesses Due to Diverticulitis. Issue 1 (2018) - Sharma, Akshay; Goyal, Sachin; Arsene, Camelia; Krishnamoorthy, Geetha; Ehrinpreis, Murray
ABSTRACT : N/A: The Fusobacterium species is known for its association with septic thrombophlebitis of the internal jugular vein (Lemierre's syndrome). Lemierre's syndrome is associated with septic emboli to the liver and lungs, often causing multiple abscesses. We present a unique case of Fusobacterium septicemia in which the bacteria invaded the portal vein through the gastrointestinal mucosa due to diverticulitis and spread hematogenously to the liver and lungs, causing abscesses. It was treated successfully with 6 weeks of antibiotics. Physicians should be aware of this rare pathogen and suspect its presence in severe pharyngitis or culture‐negative liver abscess.